Achieving business agility : strategies for becoming pivot ready in a digital world - Orvos, John (Apress, 2019)
Know how to lead and establish business agility in your organization. Benefit from clear, actionable steps based on change management truths that have been long underutilized and have limited the success of agile expansion into your business. This book provides a pragmatic framework for leading your business toward shifting to an agile mindset. Achieving Business Agility offers strategies and concrete examples to engage business executives and will teach you how to effectively execute these strategies. Whether you are a delivery executive, a change advocate, a consultant, a business leader, or a newcomer to agile, you will learn clear actions from a practical, business-oriented perspective that is vital to effect change and bring agile into your business. The book is structured in three sections. The first provides you with a deep understanding of each of four strategies. The second section tells the story of a company that applied these strategies through the eyes of several key players. The last section helps you get started applying what you learned in your own company. What You'll Learn: Get the attention of your executives by alerting them to a company problem that can impact them personally and create a sense of urgency to address it Collaborate with your executives in a way that gets them to open up and to see how their operating model is a contributing cause to the company problem Demonstrate how your executives can specifically benefit from a new agile business operating model and address the company problem Create a reinforcement structure on a larger scale to establish agile as the new standard operating model in your organization.